2011
DOI: 10.3892/mmr.2011.673
|View full text |Cite
|
Sign up to set email alerts
|

Reduced ultraviolet-induced DNA damage and apoptosis in human skin with topical application of a photolyase-containing DNA repair enzyme cream: Clues to skin cancer prevention

Abstract: Abstract. The exposure of human skin to ultraviolet radiation (UVR) results in the formation of DNA photolesions that give rise to photoaging, mutations, cell death and the onset of carcinogenic events. Photolyase (EC 4.1.99.3) is a DNA repair enzyme that reverses damage caused by exposure to UVR. We sought to investigate whether addition of photolyase enhances the protection provided by a traditional sunscreen (SS), by reducing the in vivo formation of cyclobutane-type pyrimidine dimers (CPDs) and UVR-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…This enzyme functions in diverse organisms from bacteria to vertebrates but is absent in placental mammals, including humans, that must rely solely on the less potent NER to repair UV-induced DNA lesions [ 16 ]. Sunscreen lotions containing liposomal-encapsulated bacterial photolyase or CPD-specific endonuclease have been marketed for preventing UV-induced skin damages [ 17 ], especially in patients with NER-deficiency [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme functions in diverse organisms from bacteria to vertebrates but is absent in placental mammals, including humans, that must rely solely on the less potent NER to repair UV-induced DNA lesions [ 16 ]. Sunscreen lotions containing liposomal-encapsulated bacterial photolyase or CPD-specific endonuclease have been marketed for preventing UV-induced skin damages [ 17 ], especially in patients with NER-deficiency [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical trials in 2000 12 and 2011 5 found that the addition of CPD photolyase to conventional sunscreens contributes significantly to the reduction of UV‐R‐induced DNA damage and apoptosis when applied topically to human skin. The number of UV‐B radiation‐induced CPD decreased by 40%‐45%, which demonstrates the ability of photolyase to actively repair damage 12 .…”
Section: Resultsmentioning
confidence: 99%
“…DNA damage represents one of the main causative factors of photoageing and is predominantly attributable to ultraviolet‐radiation (UV‐R) 2,5‐7 . Strategies to prevent or minimize photoageing include protection against UV‐R and preservation of antioxidant homoeostasis 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The studies by Stege et al [ 45 , 46 ] demonstrating that in human subjects topical applications of photolyase entrapped in liposomes penetrate the skin and reverse UV-induced CPDs, the pilot study by Puig et al [ 31 ] showing that Eryfotona AK-NMSC improved field cancerization significantly better than a comparator sunscreen SPF 100+, and the study by Berardesca et al [ 56 ] showing that an SPF 50 sunscreen plus photolyase was more effective than SPF 50 sunscreen alone in reducing UV-induced CPDs support that the clinical effects of Eryfotona AK-NMSC are related to photolyase activity and not simply ascribed to the degree of photoprotection.…”
Section: Discussionmentioning
confidence: 99%